2018
DOI: 10.1186/s13027-018-0188-3
|View full text |Cite
|
Sign up to set email alerts
|

Survival after cancer diagnosis in a cohort of HIV-positive individuals in Latin America

Abstract: BackgroundThis study aimed to evaluate trends and predictors of survival after cancer diagnosis in persons living with HIV in the Caribbean, Central, and South America network for HIV epidemiology cohort.MethodsDemographic, cancer, and HIV-related data from HIV-positive adults diagnosed with cancer ≤ 1 year before or any time after HIV diagnosis from January 1, 2000-June 30, 2015 were retrospectively collected. Cancer cases were classified as AIDS-defining cancers (ADC) and non-AIDS-defining cancers (NADC). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The possible scientific explanation is that HIV decreased efficacy of cellular immune responses to preserve oncologic remission, decreased tolerance of the chemotherapy as well as the radiation therapy, and increased prevalence of anemia in HIV infected women, which impairs efficacy of radiation [ 34 , 35 ]. This is evidenced by different studies like the study from Brazil showed, CCP who were treated and had a complete response, after two years of diagnosis of CC HIV was found to increase the incidence of mortality (HR: 2.2, 95% CI: 1.3–3.2, but within the first two years of diagnosis, there was no significant difference in survival of HIV positives and HIV negative [ 36 ]. The study from Botswana also revealed that HIV infection significantly increased the risk for death among all women (AHR, 1.9; 95% CI, 1.2 to 3.2) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…The possible scientific explanation is that HIV decreased efficacy of cellular immune responses to preserve oncologic remission, decreased tolerance of the chemotherapy as well as the radiation therapy, and increased prevalence of anemia in HIV infected women, which impairs efficacy of radiation [ 34 , 35 ]. This is evidenced by different studies like the study from Brazil showed, CCP who were treated and had a complete response, after two years of diagnosis of CC HIV was found to increase the incidence of mortality (HR: 2.2, 95% CI: 1.3–3.2, but within the first two years of diagnosis, there was no significant difference in survival of HIV positives and HIV negative [ 36 ]. The study from Botswana also revealed that HIV infection significantly increased the risk for death among all women (AHR, 1.9; 95% CI, 1.2 to 3.2) [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is a limitation, since a low CD4+ cell count at cancer diagnosis seems to be associated with worse survival among patients with non-AIDSdefining malignancies and could be a potential factor to explain why survival outcomes are worse among some WLWH with breast cancer. On the other hand, the influence of antiretroviral therapy or time since HIV diagnosis on cancer-related survival is less clear [53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Though this rate has been reducing from the previous estimates of 2.8% the size of Nigeria's population means 1.9 million people were living with HIV in 2018 (4). Several published literature alludes to the fact that there is increased incidence of "HIV-associated cancers" amongst HIV population consisting of both the Acquired Immune Deficiency Syndrome(AIDS)-defining cancers (Kaposi sarcoma, aggressive B-cell non-Hodgkin lymphoma and cervical cancer) and non-AIDS-defining cancers (anal, liver, oral cavity/pharynx, lungs, and Hodgkin lymphoma) (5,6). Thus, people infected with HIV are 19 times more likely to be diagnosed with anal cancer, 3 times as likely to be diagnosed with liver cancer, 2 times as likely to be diagnosed with lung cancer, about 2 times as likely to be diagnosed with oral cavity/pharynx cancer, and about 8 times more likely to be diagnosed with Hodgkin lymphoma compared with the general population (7).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, people infected with HIV are 19 times more likely to be diagnosed with anal cancer, 3 times as likely to be diagnosed with liver cancer, 2 times as likely to be diagnosed with lung cancer, about 2 times as likely to be diagnosed with oral cavity/pharynx cancer, and about 8 times more likely to be diagnosed with Hodgkin lymphoma compared with the general population (7). Survival outcomes are worse in HIV-associated than in the non-HIV cancer patients (5)(6)(7). The high population of people living with HIV in Jos, Nigeria and its known association with cancers necessitated this study which is to access the effect of HIV on cancer mortality.…”
Section: Introductionmentioning
confidence: 99%